Applying the Rasch model : fundamental measurement in the human sciences - Bond, Trevor G.; Fox, Christine M. (London : Lawrence Erlbaum Associates, 2001)
The purposes of this book are to provide an accessible overview of Rasch analyses that does not require readers to have a great deal of statistical background, to demonstrate Rasch analyses with a set of illustrative problems addressed by psychologists and educators, and to lay the groundwork for readers to perform their own Rasch analyses. In short, this book is targeted toward practitioners with relatively little background in measurement theory rather than toward measurement specialists. The author of this review believes that, in summary, the authors have done an admirable job in meeting their major goals. The book provides a nice introduction and summary for non-measurement specialists in psychology and education who simply want to learn about Rasch measurement theory. The book, however, does not provide any new insights for measurement specialists because this was not one of the authors' goals. -- This book was designed to introduce the "how" of Rasch measurement to those who already had thought at least a little about the "why". First, the philosophy and mathematical theory underlying Rasch modeling are clearly in empathy with what many practicing researchers are trying to discover from the research data. Second, the Rasch-based techniques used had very firm bases in general principles of mathematics and measurement. The fundamental underlying mathematical principles, what some researchers have called probabilistic conjoint measurement, are the keys to the success of this approach. The Rasch model provides useful approximations of measures that help us understand the processes underlying the reason why people and items behave in a particular way.
Appendix B: Rasch resources